Educação, livros e bibliotecas na Fundação CASA São Paulo - Amorim, Kacianna Patrícia de Jesus Barbosa e (2024)
The present work presents a historical overview of books and libraries, as well as a study on the practice of reading over the centuries up to the present day, highlighting the relevance of reflecting on the right to education and reading for all citizens, including those incarcerated. For this reason, contemplating the situation of orphaned boys and girls, abandoned or living on the streets, or interned in institutions due to legal conflicts, becomes urgently necessary for the continuity of the initial history of books and libraries: books exist because of their readers! The aim of this doctoral work is to investigate the existence of libraries at CASA Foundation São Paulo and the perception of adolescents and young people regarding education and reading practices experienced in these locations. This research adopts a qualitative approach, utilizing field research as the method, conducted in two juvenile detention centers, one male and one female, both recommended by the CASA Foundation in São Paulo and located in the Capital. Data collection involved the observation of spaces and practices, open interviews with educators from the Foundation and the São Paulo Department of Education, as well as the application of the focus group technique for interaction with the detained adolescents in these environments. Results indicate the existence of libraries not only in the Foundation-recommended spaces but also in various other units throughout the Capital and Greater São Paulo. There is a significant effort by the educational and managerial teams to maintain, organize, and make these spaces available to adolescents, particularly through the constant renewal of their collections via donations. The interviewed teachers work on promoting reading, but the structures of their classes still represent a modest incentive for their students to appropriate written culture.